Serum iron concentration and total iron binding capacity in patients of oral squamous cell carcinoma - Hossain, Shakhawat; Molla, Motiur Rahman; Akhter, Mahmuda (Bangladesh Journal of Pharmacology, 2007)
The serum iron concentration and Total Iron Binding Capacity (TIBC) status of 24 patients of oral squamous cell carcinoma (OSCC) were compared with the findings of 13 healthy subjects. OSCC was found to have association with low serum iron level. More patients were found to be with significantly lower iron content in serum (p&lt0.05). But no association between serum TIBC and increased risk of cancer was found (p&gt0.05). Irrespective of age, sex, smoking and betel nut chewing habit of subjects, low serum iron level significantly increase the risk of oral malignancy.